Implementasi Kurikulum Merdeka dalam Pembelajaran PAI - Azis, Abd (AL-BURHAN, 2024)
This study aims to describe the implementation of the independent curriculum in PAI learning. This type of research is literature research, with a qualitative descriptive approach. The main data are taken from books and journals that are directly related to the issue of the independent curriculum. Skunder data is taken from books and journals that have an indirect relationship and or that support the main data. Data is collected by documentation techniques. After the data is collected, it is then analyzed using content analysis techniques and inductive - deductive. This study concludes that the independent curriculum is the right solution for the education process today. In the independent curriculum, education is focused on students so that they are active and creative. In addition, the material obtained is more real so that it will be more imprinted in the student's soul and that is how education should be. PAI learning in the independent curriculum other than through the project model, schools and / or madrasahs can cooperate with other educational institutions such as Islamic boarding schools or madrasah diniyah. This is done by adjusting teaching materials, allocation of time and expected competencies as well as the entire administration of learning.Keywords: PAI, Curriculum Merdeka, PAI di Curriculum Merdeka